Optical observations geomagnetically conjugate to sprite-producing lightning discharges - R. A. Marshall; U. S. Inan; T. Neubert; A. Hughes; G. Sátori; J. Bór; A. Collier; T. H. Allin (Annales Geophysicae, 2005)
Theoretical studies have predicted that large positive cloud-to-ground discharges can trigger a runaway avalanche process of relativistic electrons, forming a geomagnetically trapped electron beam. The beam may undergo pitch angle and energy scattering during its traverse of the Earth's magnetosphere, with a small percentage of electrons remaining in the loss cone and precipitating in the magnetically conjugate atmosphere. In particular, N2 1P and N2+1N optical emissions are expected to be observable. In July and August 2003, an attempt was made to detect these optical emissions, called "conjugate sprites", in correlation with sprite observations in Europe near . Sprite observations were made from the Observatoire du Pic du Midi (OMP) in the French Pyrenées, and VLF receivers were installed in Europe to detect causative sferics and ionospheric disturbances associated with sprites. In the Southern Hemisphere conjugate region, the Wide-angle Array for Sprite Photometry (WASP) was deployed at the South African Astronomical Observatory (SAAO), near Sutherland, South Africa, to observe optical emissions with a field-of-view magnetically conjugate to the Northern Hemisphere observing region. Observations at OMP revealed over 130 documented sprites, with WASP observations covering the conjugate region successfully for 30 of these events. However, no incidences of optical emissions in the conjugate hemisphere were found. Analysis of the conjugate optical data from SAAO, along with ELF energy measurements from Palmer Station, Antarctica, and charge-moment analysis, show that the lightning events during the course of this experiment likely had insufficient intensity to create a relativistic beam. Keywords. Ionosphere (Ionsophere-magnetosphere interactions; Ionospheric disturbances; Instruments and techniques)